JOB SATISFACTION IN A TOURIST RESORT IN PORTUGAL - Xana Mader (Journal of Spatial and Organizational Dynamics, 2018)
Job satisfaction is one of the most widely studied variables in the field of organizational behavior. The touristic sector has been an increasingly economically relevant sector in Portugal. An empirical study was developed in a tourist Resort in Algarve, in order to analyse the level of the employees’ job satisfaction. A specifically questionnaire developed to this sector was applied to 221 employees. The employees who have been in the organization for more years feel less job satisfaction and are overall less satisfied with the organization; employees who have completed a higher education have higher job motivation levels. Future studies should apply this holistic job satisfaction questionnaire, in order to could compare results in this activity sector.